2003
DOI: 10.1242/jeb.00661
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of homing in the fiddler crabUca rapax2. Information sources and frame of reference for a path integration system

Abstract: In order to return to a place they have previously visited, many animals use a form of coding of their movements, called path integration by Mittelstaedt and Mittelstaedt (1980), wherein information arising from the animal's own movement is used to update the animal's memory of its position continuously in the form of a vector joining the animal's current location with the goal (for example reviews, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 54 publications
(43 reference statements)
1
55
0
1
Order By: Relevance
“…In addition to color discrimination, polarization sensitivity is common in several marine organisms, and its role is similar to color vision in enhancing contrast and conspicuousness, intraspecific signaling, and object identification (Cronin et al, 2003;Glantz and Schroeter, 2006;Glantz, 2008). In fiddler crabs, polarization sensitivity can apparently be used as a celestial direction cue for orienting to the crabs' home beach (Herrnkind, 1968;Chiussi and Diaz, 2002), although it appears to play no role in finer-scale navigation by path integration (Layne et al, 2003). Typically in insects, the dorsal rim area contains UV-sensitive photoreceptors which are also polarization sensitive, coinciding with the fact that natural light tends to be more polarized at shorter wavelengths.…”
Section: Spatial Distribution Of U Pugilator Opsinsmentioning
confidence: 99%
“…In addition to color discrimination, polarization sensitivity is common in several marine organisms, and its role is similar to color vision in enhancing contrast and conspicuousness, intraspecific signaling, and object identification (Cronin et al, 2003;Glantz and Schroeter, 2006;Glantz, 2008). In fiddler crabs, polarization sensitivity can apparently be used as a celestial direction cue for orienting to the crabs' home beach (Herrnkind, 1968;Chiussi and Diaz, 2002), although it appears to play no role in finer-scale navigation by path integration (Layne et al, 2003). Typically in insects, the dorsal rim area contains UV-sensitive photoreceptors which are also polarization sensitive, coinciding with the fact that natural light tends to be more polarized at shorter wavelengths.…”
Section: Spatial Distribution Of U Pugilator Opsinsmentioning
confidence: 99%
“…Despite the current lack of comparative data on modulating velocity between a start and stop, systems such as the predatory attacks of suction-feeding fishes and fiddler crabs returning to their home burrows (Layne et al, 2003) may prove to be useful model systems for future investigation of starts and stops in which experimenters can manipulate distance and have animals come to a stop at a predictable location.…”
Section: Ecological Relevance Of Stoppingmentioning
confidence: 99%
“…However, it is becoming increasingly apparent that despite their relatively small brains and generally shorter distances traveled (the monarch butterfly, Danaus plexippus, not withstanding; Mouritsen et al, 2013), many arthropod species also display an impressive navigational ability (Cheng, 2012;Collett and Graham, 2004;Boles and Lohmann, 2003;Layne et al, 2003). Indeed, both honey bees (Apis mellifera; Menzel et al, 2005) and an Australian ant species (Myrmecia croslandi; Narendra et al, 2013) have been shown to be able to return to their nests even after experimental displacement to unfamiliar locations, suggesting a cognitively rich navigational capacity.…”
Section: Introductionmentioning
confidence: 99%